Examining the Potential of Type V Dess for the Solvent Extraction of Metal Ions - Olea-Chandia, F (Royal Society of Chemistry, 2025)
Growing interest in sustainable and efficient metal ion separation has led to the exploration of non-ionic deep eutectic solvents (DESs), also known as type V DESs, as promising alternatives to conventional organic phases in solvent extraction (SX). This work summarizes recent developments, focusing solely on the use of non-ionic DESs and excluding ionic DESs, for the separation of metal ions from synthetic and real leachates. The review does not aim to exhaustively cover all studies but focuses on the molecular mechanisms of SX, how inherent properties of DESs influence these mechanisms, and how they can be harnessed to improve the separation selectivity. It further highlights the physico-chemical properties of DESs in SX and compares them with traditional systems, emphasizing similarities and new opportunities. The overall aim is to clarify the potential and limitations of type V DESs in SX, including their often touted credentials as “green solvents”, and to offer guidelines for their practical use and addressing skepticism towards novel solvents in hydrometallurgy. © 2025 The Royal Society of Chemistry.